Independent Variables Affecting Outcome of Carpal Tunnel Release Surgery. (May 2018) - Watchmaker, Jacqueline D.; Watchmaker, Greg P.
Background: In making the decision to undergo carpal tunnel release (CTR), patients may consider probability of symptom resolution. Prior studies have examined potential preoperative variables that might influence the postoperative outcome. Few studies, however, contain the sample size, prospective design, and high participant completion rate to provide solid data from which to counsel patients. The purpose of this study was to prospectively evaluate factors that have been implicated or dismissed in past studies as sources of outcome variation following CTR surgery and provide patient-relatable facts that the surgeon might use in preoperative patient counseling.Methods: One thousand thirty-one consecutive patients undergoing open CTR were prospectively enrolled. Preoperative frequency of daytime numbness, nighttime awakening, and duration of symptoms were recorded in addition to physical exam, height, weight, sex, history of diabetes, history of thyroid disease, and severity of electrodiagnostic findings. After surgery, patients reported percent resolution of numbness at defined intervals.Results: Age and sex are the only independent factors that predict the degree of resolution of numbness 6 months following surgery. All other studied variables are not independent factors nor are any paired combinations of factors. Below the age of 50, the average reported resolution of daytime numbness by 6 months is 97.3% (men 91.8% and women 99.4%). After age 50, there is a linear 0.77% decline in average resolution of daytime numbness per year.Conclusions: Age and sex but no other studied factors predict resolution of daytime numbness in a multivariate model of patients undergoing CTR.